Прогнозирование геологической среды земной коры по материалам ГСЗ и петрофизического термобарического исследования минерального вещества - Корчин, В.А.; Буртный, П.А.; Карнаухова, Е.Е. (Геодинаміка, 2009)
Some features of methodical means of petrovelocity thermobaric modeling have been considered. An example of the construction of a deep petrovelocity model of a crust part of the Ukrainian Shield is given and analysed.